Potensi Jamur Asal Rizosfer Tanaman Cabai Rawit (Capsicum frutescens l.) Sehat dari Desa Bumbungan Kecamatan Banjarangkan Kabupaten Klungkung dalam Upaya Mengendalikan Penyakit Layu Fusarium secara In Vitro - MAULANA, FERDIANSYAH DWI; SUDARMA, I MADE; SUNITI, NI WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.5, No.2, April 2016, 2016)
The potential of rhizosphere fungi from health cayenne pepper plant (Capsicum frutescens L.) from Bumbungan Village to control the wilt disease Fusarium in vitro The objectives of the research were to find out the potential and level domination (prevalance) of rhizosphere fungi from health cayenne pepper plant (Capsicum frutescens L.) to control the wilt disease Fusarium. It was done by using the in vitro inhibition test of rhizophere fungi againts the Fusarium oxysporum f.sp. capsici with dual culture technique. The study included 1) rhizosphere soil sampling of health cayenne pepper plants; 2) isolation and identification of soil fungi; 3) isolation of the pathogen Fusarium oxysporum f.sp capsici; 4) purification of pathogenic isolates of Fusarium oxysporum f.sp capsici; 5) prevalence of fungal isolates; 6) testing the inhibition of rhizosphere fungi on the growth of the fungus Fusarium oxysporum f.sp. capsici. The result showed that the identified rhizosphere fungi were the genus of Aspergillus spp., Penicillium spp., Trichoderma spp. The prevalence of fungi in the rhizosphere that dominate the healthy cayenne pepper plant is the genus of Penicillium spp. and Aspergillus spp. which have the same prevalence rate of each, 42.1 %. while the fungus Trichoderma spp. has prevalence rate 15,8 % . The results showed that all the rhizosphere fungi have potential to control wilt disease Fusarium oxysporum f.sp. capsici with different levels of inhibition. Based on the results of this study, further research needs to be done in order to apply directly the identified antagonist fungi to plant that already affected with wilt diseas
Keywords: Cayenne pepper; rhizosphere; Fusarium oxysporum f.sp. capsici